Sistema financeiro, crescimento econômico e desigualdades regionais no Espírito Santo : uma análise espacial para os municípios - Araújo, Rodolfo Fernandes (2012)
The objective of this work is to study the behavior and performance of the different profiles of the financial system (related to the amount of agencies, funds, deposits, among other variables) in the Espírito Santo as an important factor to explain the regional disparities in the state. Based on the relationship between growth and development defined by post Keynesian theory, the financial system is one of the key players for regional development through the financing of productive activities. Moreover, regional disparities are exacerbated banking strategies that banks have differentiated according to the locality in which they live, known as the theory of circular and cumulative causation (Myrdal, 1965). In general, the main objective of this work is to identify the regions of the Espírito Santo which are characterized by economic dynamism and has a developed financial system and willing to offer greater amounts of credit. To achieve this, the methodological framework was composed of two analyzes. First, we performed a principal component analysis and cluster for micro Espírito Santo, and later, a spatial analysis using the technique of factor analysis to municipalities. Factor analysis, which in turn is unprecedented for an analysis of the topic in question (the relationship between growth and finance), was constructed by economic and financial variables, covering the space comprised by 78 municipalities. By employing this technique it was possible to construct an index that indicates the financial development potential (FDP) for of the municipalities. The results reveal the strong disparities between the capixabas municipalities noting that the financial system is concentrated in regions characterized by having economic dynamism and social development, revealing important explanatory factor of regional imbalances in the local economy